The Medicinal Plant Pair Bupleurum chinense-Scutellaria baicalensis - Metabolomics and Metallomics Analysis in a Model for Alcoholic Liver Injury - Zefang Dang; Qianhua Li; Shujun Sun; Yang Wang; Rui Lin; Yongyu Zhang; Yongyu Zhang; Jianye Dai; Jianye Dai; Ningning Zheng (Frontiers Media S.A., 2019)
Traditional Chinese Medicine (TCM), a complex natural herbal medicine system, has increasingly attracted attention from all over the world. Most research has illustrated the mechanism of TCM based on the active components or single herbs. It was fruitful and effective but far from satisfactory as it failed to gain insights into the interactivity and combined effects of TCM. In this work, we used Bupleurum chinense (B. chinense DC, a species in the genus Bupleurum, family Apiaceae) and Scutellaria baicalensis (S. baicalensis Georgi, a species in the genus Scutellaria, family Lamiaceae), an herbal pair in TCM, to illustrate the combined effect. We compared the diverse effects between the B. chinense-S. baicalensis herbal pair and its compositions in an animal model of Alcoholic Liver Injury to highlight the advantages of the formula. Biochemical and histological indicators revealed that the effect of B. chinense-S. baicalensis was better than its individual parts. Furthermore, metabolite profiling of the serum, liver tissue, and feces were conducted to reveal that the herbal pair largely presented its effects through enhanced tissue penetration to maintain liver-located intervention with less global and symbiotic disturbance. Furthermore, we analyzed the distribution of the metal elements in extracts of the serum and liver tissue and found that the herbal pair significantly regulated the distribution of endogenous selenium in liver tissue. As selenium plays an important role in the anti-oxidative and hepatoprotective effects, it may be the reason for combined effects in BS formula. This research could open new perspectives for exploring the material basis of combined effects in natural herbal medicine.